Joanne M.A. Murphy (ed.), Death in Late Bronze Age Greece: Variations on a Theme. - Alvarez, Laura (Journal of Greek Archaeology, 2022)
Joanne M.A. Murphy (ed.), Death in Late Bronze Age Greece: Variations on a Theme. pp. 360. Oxford: Oxford University Press. ISBN 978-0-19092-606-9, hardcover £68.